1990
DOI: 10.1002/jhet.5570270230
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Cα,O‐dilithiooximes with functionalized carbonyl compounds. Part 2. Reaction with α‐chloroketones and α,β‐unsaturated aldehydes and ketones

Abstract: The reaction of Cα,O‐Dilithiooximes 2 and α‐chloroketones afforded 5‐(hydroxymethyl)‐Δ2‐soxazolines 4. α,β‐Unsaturated aldehydes and ketones reacted with 2 to give the corresponding acyclic 1,2‐addition products 5. The latter were cyclized with phosphorus pentoxide to 5‐vinyl‐Δ2‐isoxazolines 6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In order to synthesize compounds which had alpha hydrogens at the 3-position of the oxazine we needed another route. In 1990 Jordanian workers reported that they could make isoxazolines through oxime dianions probably via an epoxide intermediate (7). Treatment of die acetophenone oxime dianion with phenacyl bromide gave 3,5-diphenylisoxazoline-5-methanol in good yield.…”
Section: Figure 10 Possible Isomerization Of Cyclic Nitroso-olefinsmentioning
confidence: 99%
“…In order to synthesize compounds which had alpha hydrogens at the 3-position of the oxazine we needed another route. In 1990 Jordanian workers reported that they could make isoxazolines through oxime dianions probably via an epoxide intermediate (7). Treatment of die acetophenone oxime dianion with phenacyl bromide gave 3,5-diphenylisoxazoline-5-methanol in good yield.…”
Section: Figure 10 Possible Isomerization Of Cyclic Nitroso-olefinsmentioning
confidence: 99%
“…Although such a synthesis of the cis-fused 1,2-oxazadecaline system has not, to our knowledge, been reported in the literature, the precedents of 1,2-addition of α C -mono- and α C,O -bislithiated acetophenone oximes to ketones, 17 the efficiency of this approach, and the ready availability of benzoquinone and ethyl pyruvate, made it an attractive direction for investigation.…”
mentioning
confidence: 99%
“…base was required to overcome the coordination of the lithium base to the oxime. 17d LiTMP proved to be the base of choice, as no or very little product was observed with other bases. Analysis of the crude reaction mixture by 1 H NMR spectroscopy prior to quenching with acetic acid revealed presence of quinol 18 and silyl enol ether 19 , along with enone 15 , suggesting that 18 and 19 may be intermediates en route to 15 .…”
mentioning
confidence: 99%